Navigating Contemporary Islamic Reason: An Epistemological Analysis of Mohammed Arkoun - Hidayatulloh, Taufik (Jurnal Pemikiran Islam, 2024)
This research examines the profound epistemological critique and semiotic analysis of Islamic thought by Mohammed Arkoun, focusing on his challenge to traditional paradigms within Islamic scholarship. Arkoun argues that Islamic reason has historically been confined by dogmatic interpretations, which has limited its evolution in the context of modern challenges. Employing a historical-critical methodology and a semiotic approach, Arkoun seeks to uncover layers of meaning that have been obscured by traditionalist readings and to demonstrate the need for a more critical and dynamic interpretation of Islamic texts. Arkoun’s critique explores the historical, linguistic, and cultural contexts that shape Islamic thought, advocating for an approach that acknowledges the influence of these factors on religious interpretation. His analysis reveals how Islamic thought, if unchallenged and unchanged, risks stagnation in a rapidly evolving world. Through a detailed examination of Quranic discourse and the application of modern critical theories, Arkoun proposes a deconstruction of the 'thinkable' and challenges the 'unthinkable' within Islamic thought. This study emphasizes the importance of revisiting the epistemological foundations of Islamic knowledge to foster a more inclusive, reflective, and adaptive intellectual tradition. Arkoun's work provides valuable insights into the potential for Islamic thought to engage more profoundly with contemporary issues, urging a reform that embraces critical inquiry and the exploration of diverse interpretative possibilities.